The Effect of Affiliate Marketing and Celebrity Endorsement on Purchase Intention Through Customer Trust: A Study on Gen Z TikTok Shop Customer in Purwokerto - Lista Dea Safitri; Muchammad Agung Miftahuddin; Herny Justiana Astuti; Alfato Yusnar Kharismasyah (SAFE-Network, 2026)
This study aims to analyze the influence of Affiliate Marketing and Celebrity Endorsement on Purchase Intention of TikTok Shop consumers with Customer Trust as a mediating variable. The method used in this study is quantitative with a survey approach, involving 131 Gen Z respondents in Purwokerto who actively use TikTok Shop. Data analysis was conducted using SEM-PLS. The results of the hypothesis testing indicate that Affiliate Marketing, Celebrity Endorsement, and Customer Trust have a positive and significant influence on Purchase Intention. In addition, Customer Trust is proven to function as a mediating variable for Affiliate Marketing and Celebrity Endorsement on Purchase Intention. This study provides important insights for business actors in understanding the dynamics of digital marketing on the TikTok Shop platform, especially in utilizing Affiliate Marketing and Celebrity Endorsement strategies to increase Purchase Intention. These findings also emphasize the importance of the role of Customer Trust as a bridge connecting marketing strategies with consumer purchasing decisions. Therefore, strengthening the relationship between brands and consumers through increasing trust can be key to achieving success in a competitive digital market. Practically, these findings can be used by business actors to design more effective marketing strategies on TikTok Shop, as well as contribute to the development of consumer behavior and digital marketing theories.